Building online learning communities within a China-UK partnership programme - Burch, Stuart; Bunnag, Stella (Journal of Academic Language and Learning, 2023)
This paper outlines the strategies used within an online study skills course designed to build learning communities across borders in a UK-China Transnational Education (TNE) programme. It presents the fundamental aspects of “community” which include bonding, inclusion, validation, student-centred learning, engagement and a sense of belonging. These are demonstrated through a case study of an ongoing partnership between Nottingham Trent University and the Communication University of China. This collaboration has embedded “community” principles in three key areas: dynamic use of social media, specifically WeChat; an active social programme; and online community-building through classwork activities. These are explained and evaluated using feedback from a group student interview together with survey responses. The transferrable findings help identify the core principles needed to build successful learning communities, as well as opportunities for future development.